Two-Objective Optimization of Tidal Array Micro-Sitting Accounting for Yaw Angle Effects - Can Zhang; Yichi Zhang; Jisheng Zhang; Xiaoming Cheng; Xiangfeng Lin; Chengsheng Wu; Zihan Ding (Journal of Marine Science and Engineering, 2025)
Power output and economic cost are two critical factors influencing the layout of tidal stream turbine arrays. To identify the optimal configuration, this study establishes a two-objective optimization framework that simultaneously considers these factors. Both the spatial location and yaw angle of each turbine are optimized to enhance overall power output, while the total length of submarine cables, which is used to transmit electricity from the turbines to the onshore power station, is adopted as the metric for economic cost. The Huludao water area is selected as the study domain. A 12-turbine array is examined under varying weight coefficients to investigate the trade-off between maximizing power output and minimizing economic cost. The optimization results show that submarine cable length decreases linearly as its economic weight coefficient increases, while the array’s power output exhibits a stepwise decline. This indicates that, with carefully chosen weight coefficients, economic costs can be significantly reduced without a proportional sacrifice in power output. Furthermore, increasing the number of turbines connected by a single cable not only enhances power output but also reduces total cable length, thereby improving the overall profitability of the optimized array layout.